A corpus analysis of frequently occurring words and their collocations in high-impact research articles in education - Sharmine Farahin Bahtiar,; Arshad Abd Samad,; Abu Bakar Mohamed Razali,; Ho, Yoong Wei (Penerbit Universiti Kebangsaan Malaysia, 2020)
In research writing, the importance of formulaic sequences (FS) or collocations and the need for writers to adapt and utilise these phrasal constructions in their writing cannot be denied. However, English as a second or a foreign language (ESL/EFL) writers often have difficulty in finding the right words or phrases in writing good academic research papers due to limited vocabulary and the lack of native-like fluency. There is also the concern that they are unaware of the rhetorical structure of academic research papers, which can hamper the organization of ideas and flow of writing and lead to messy and unclear production of language. Formulaic sequences and collocations of words represent useful phrasal constructions that writers use to fluently and efficiently express their intended communicative purposes. In this regard, this study uses corpus analysis to list collocations commonly used in high-impact journals written in the field of education. The study also categorises these collocations according to their communicative purposes, referred to as moves and steps, in the rhetorical structure of the Introduction of research articles. The final list which focussed on ten node words from 40 highimpact journal articles consists of 3 to 12 word phrases found in the Introduction section of these articles. They were then categorised according to their specific functions based on an adapted Introduction Move Framework of the Create a Research Space (CARS) schema (Swales 2004) and common moves in the Introduction section of the Academic Phrasebank (Morley, 2014).